PERENCANAAN EMBUNG TAMANREJO KECAMATAN SUKOREJO, KABUPATEN KENDAL - Bachtiar Khoironi Wibowo; Arvie Narayana; Abdul Kadir; Dwi Kurniani (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2014)
The population and community activities that lead to increased irrigation water demand is increasing and causing problems between water balance demand and water availability. To overcome this case was built water building of small dam. Tamanrejo small dam situated on the Kajar River, Sukorejo Kendal Regency. Tamanrejo small dam is planned to meet the needs of irrigation water in the District Sukorejo, irrigation area that will be served an estimated area of 750 acres. Discharge mainstay Kajar River calculated based FJ. Mock method with the probability of 20% is not being met. In Agustus until November there is a shortage of water at 108.493,75 m3. Small dam volume of 126.073,69 m3 is at an elevation of +140,00 m to +147,00 m. The result of water balance calculations indicate that the volume of 126.073,69 m3 can to meet the need of irrigation water when the river have flow shortage. Calculation results obtained irrigation water needs 1,54 l/sec/acres as irrigation water requirement rate on average. Construction of a small dam Tamanrejo be making use of the spillway and dam embankment body. Determination of dimensions small dam Tamanrejo use flood discharge plan from the HSS Gama I method of 83,189 m3/sec with a return period of 50 years. The planned small dam 11 m high, with a base elevation ponds +140,00 m, +151,00 m small dam crest elevation. Small dam crest width of 5,00 m, upstream slope of 1:3 and downstream slope of 1:2,25. In planning small dam Tamanrejo used ogee type open spillway (overflow spillway) with a width of 25 m, length 13 m and elevation crest spillway at +147,00 m, using an eject USBR type III with a length of 5,00 m. Plan Implementation time is 24 weeks with work plan budget of Rp. 6,258,700,000.00 (Six Billion Two Hundred Fiffty Eight Million Seven Hundred Thousand Rupiah). Conclusion with built small dam can overcome the shortage of irrigation water.